Eosinophilic Myocarditis due to Toxocariasis: Not a Rare Cause - Shunichi Shibazaki; Shunsuke Eguchi; Takashi Endo; Tadamasa Wakabayashi; Makoto Araki; Yoshiaki Gu; Taku Imai; Kouji Asano; Norihide Taniuchi (Case Reports in Cardiology)
Myocarditis is a clinically important disease because of the high mortality. From the perspective of treatment strategy, eosinophilic myocarditis should be distinguished from other types of myocarditis. Toxocariasis, caused by Toxocara canis or Toxocara cati, is known as a cause of eosinophilic myocarditis but is considered rare. As it is an unpopular disease, eosinophilic myocarditis due to toxocariasis may be underdiagnosed. We experienced two cases of eosinophilic myocarditis due to toxocariasis from different geographical areas in quick succession between 2013 and 2014. Case 1 is 32-year-old man. Case 2 is 66-year-old woman. In both cases, diagnosis was done by endomyocardial biopsy and IgG-ELISA against Toxocara excretory-secretory antigen. Only a corticosteroid was used in Case  1, whereas a corticosteroid and albendazole were used in Case  2 as induction therapy. Both patients recovered. Albendazole was also used in Case  1 to prevent recurrence after induction therapy. Eosinophilic myocarditis by toxocariasis may in actuality not be a rare disease, and corticosteroid is an effective drug as induction therapy even before use of albendazole.